1996
DOI: 10.1093/brain/119.5.1449
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of acute and chronic ischaemic neuropathy in atherosclerotic peripheral vascular disease

Abstract: The peripheral nerve pathology in ischaemic limbs with atherosclerotic peripheral vascular diseases (PVD) is difficult to ascertain because of the limited number of reports. In addition, it has been debated whether chronic ischaemia per se could cause morphological abnormalities in peripheral nerves. In this prospective study, we examined pathological findings in the sural, saphenous, deep peroneal, superficial peroneal and tibial nerves, taken from seven acutely and nine chronically ischaemic amputated legs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 0 publications
2
33
0
1
Order By: Relevance
“…Distal sensory changes and sometimes distal weakness are found. After acute ischemia, electrophysiological [60]and pathological [62]examination shows axonal degeneration of nerves of the distal portion of the limb. Sensory amplitudes are usually more severely affected [60, 61, 63, 64].…”
Section: Clinical Ischemic Neuropathymentioning
confidence: 99%
See 2 more Smart Citations
“…Distal sensory changes and sometimes distal weakness are found. After acute ischemia, electrophysiological [60]and pathological [62]examination shows axonal degeneration of nerves of the distal portion of the limb. Sensory amplitudes are usually more severely affected [60, 61, 63, 64].…”
Section: Clinical Ischemic Neuropathymentioning
confidence: 99%
“…Complaints are predominantly sensory, whereas motor abnormalities are less frequent [95]. Severity rather than duration of ischemia plays a key role in the development of the neuropathy [62, 97]. There is a correlation between the severity of peripheral arterial disease and the number of patients with neuropathy [98].…”
Section: Clinical Ischemic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have also reported that hypoxia/ischemia injury plays an important role in the development of peripheral neuropathy [3,4]. Morphologically, ischemic nerves reveal various pathological abnormalities, including demyelination and remyelination, axonal degeneration and regeneration, focal, multifocal, or diffuse loss of nerve fibers, and endoneurial edema [5].…”
mentioning
confidence: 99%
“…1,4,5) However, no studies have indicated that atherosclerosis affects peripheral nerves in other (nonischaemic) parts of the body. In this study, patients with coronary artery disease showed a greater predisposition to peripheral neurological problems than those without such disease (44% versus 7% respectively).…”
mentioning
confidence: 99%